Medical Biophysics - CĂLINESCU, Octavian (2024)
This book was written for first year medicalstudents, in particular, those studying medicinein English at the “Carol Davila” University ofMedicine and Pharmacy Bucharest. However,even if you, the current reader, are not in thatposition, this book might still be for you if areinterested in biophysics or the functioning of thehuman body in general.